Elements of a theory of social time.A Schützian approach - Sebald, Gerd (SocietàMutamentoPolitica, 2016)
The paper discusses in the first place the Bergson’s pragmatic concept of time and successively the Husserl’s concept of time and the lifeworld to define their influences for Alfred Schutz whose considerations on time started from Henry Bergson’s philosophy of duration. The Austrian sociologist uses Husserl’s considerations on the inner-time consciousness as a complement of Bergson’s theory. It’s a well-know fact that time is a foundamental topic for Schutz expecially in his Fragments toward a Phenomenology of Music (1944). Schutz’s phenomenological research on music takes in to account the Bergsonian connection of mind and body, of (inner ) time and space and their theoretical characterizazion. The paper examines finally Ilja Srubar’s differentiation between constituted an produced time. Coming a conclusion the paper distinguishes analitically a multiplicity of forms of time and the types of mechanism for their formation trying to describe the kind of interrelations are to found between these different forms as necessary elements in order to conceive a sociological theory of time.